The Impact of GCG and Financial Ratios on Earnings Management in Sharia Banks - Zaini Ibrahim; Soliyah Wulandari; Sanawi Sanawi; Yayu Putri Senjani (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2024)
The research aims to find empirical evidence of the factors influencing earnings management in Sharia banking in Indonesia. The factors are Good Corporate Governance and financial ratios, which include managerial ownership, independent commissioners, audit committees, audit quality, financial leverage, profitability, and free cash flow. The object of this research is Sharia Commercial Banks in Indonesia. The sample period in this study is from 2017 to 2021. The sample selection was carried out using a purposive sampling method. The final sample used in this study was 41 observations. Secondary data is collected from the financial statements of each Islamic bank. The data is processed using a statistical test of multiple regression models. The results of this study indicate that managerial ownership, independent commissioners, and free cash flow affect earnings management in Sharia banking in Indonesia. Meanwhile, audit committee, audit quality, financial leverage, and profitability do not affect earnings management in Sharia banking in Indonesia